2021
DOI: 10.3389/fvets.2021.653129
|View full text |Cite
|
Sign up to set email alerts
|

Age and Staphylococcus aureus Inoculation Route Differentially Alter Metabolic Potential and Immune Cell Populations in Laying Hens

Abstract: In 2018 and 2019, Staphylococcus aureus was isolated from multiple post-molt commercial laying hens with unusually high mortality. A challenge study was conducted to elucidate the role of S. aureus in this disease outbreak and the work herein represents the assessment of immunological responses in laying hens experimentally infected with S. aureus isolates from these cases. A total of 200 laying hens at 22 or 96 weeks of age (100/ age group) were assigned to 1 of 4 experimental inoculation groups (negative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Staphylococci are ubiquitous in poultry farms and hatcheries and are natural inhabitants of the chicken skin and mucous membranes but have also been associated with secondary infections ( 12 ). The 16S metagenomics and isolation results in this study showed a high diversity of Staphylococcus species on skin and environmental samples from FUDS negative and control flocks as compared to the FUDS positive group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococci are ubiquitous in poultry farms and hatcheries and are natural inhabitants of the chicken skin and mucous membranes but have also been associated with secondary infections ( 12 ). The 16S metagenomics and isolation results in this study showed a high diversity of Staphylococcus species on skin and environmental samples from FUDS negative and control flocks as compared to the FUDS positive group.…”
Section: Discussionmentioning
confidence: 99%
“…Although little research has been done on the etiology of FUDS, a correlation between disease and S. hyicus abundance has been observed ( 7 ). The production losses due to Staphylococcus infections in poultry (egg laying or meat birds) have been associated with lameness, drop in egg production ( 9 , 12 ), increased mortality, and condemnation of carcasses at slaughter facilities ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using poultry cells, specifically, has included immortal cell culture lines, such as chicken macrophage-like cells (3), embryo fibroblast cells (4), and primary brain cells (5). More recent Seahorse optimization and disease research has been published using PBMCs isolated from humans (23,24) and human cell lines (25), and research using laying hen PBMCs within the Seahorse assay has been recently published by the current lab group (26), but no optimization of chicken PBMCs has been published. Peripheral blood mononuclear cells are, however, suitable and well-published cells to use in immune cell metabolic and disease research (25), and are an ideal option for Seahorse analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a heterogenous population of immune cells including leukocytes, monocytes, thrombocytes, and erythrocytes ( 24 ), combining real-time metabolic assays with immune profiling by flow cytometry allows for the potential identification of cell populations responsible for observed metabolic shifts. This has been done previously in assessing hen responses to Staphylococcus aureus but has not been similarly applied to Eimeria infection or genetic line comparisons of Eimeria immune responses ( 25 ). The study objective was to evaluate immunometabolic shifts and underlying cell profiles in chicken PBMC isolated from legacy genetic lines identified as being resistant (Fayoumi M5.1) and susceptible (Leghorn Ghs6 and Ghs13) during Eimeria challenge.…”
Section: Introductionmentioning
confidence: 99%